2021
DOI: 10.1101/2021.09.17.21263343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Butyrate and related epigenetic changes link Parkinson’s disease to inflammatory bowel disease and depressive symptoms

Abstract: Background The gut microbiome and its metabolites can impact brain health and are altered in Parkinson's disease (PD) patients. It has been recently demonstrated that PD patients have reduced fecal levels of the potent epigenetic modulator butyrate and its bacterial producers. Here, we investigate whether the changes in the gut microbiome and associated metabolites are linked to PD symptoms and epigenetic markers in leucocytes and neurons. Methods Stool, whole blood samples, and clinical data were collecte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…26 Several studies have linked lower levels of SCFA-producing taxa with gut inflammation, epigenetic changes, and depressive symptoms in PD. [27][28][29][30] In concordance, decreased levels of the SCFA-producing genera Butyricoccus, Colidextribacter and the families Butyricoccaceae and Veillonellaceae were found in the current study. On the other hand, the SCFA-producing family Rikenellaceae was increased in PD.…”
Section: Comparison With Previous Studiessupporting
confidence: 86%
“…26 Several studies have linked lower levels of SCFA-producing taxa with gut inflammation, epigenetic changes, and depressive symptoms in PD. [27][28][29][30] In concordance, decreased levels of the SCFA-producing genera Butyricoccus, Colidextribacter and the families Butyricoccaceae and Veillonellaceae were found in the current study. On the other hand, the SCFA-producing family Rikenellaceae was increased in PD.…”
Section: Comparison With Previous Studiessupporting
confidence: 86%
“…Butyrate can inhibit histone deacetylase, thereby promoting histone acetylation and subsequent chromatin relaxation and gene expression (reviewed in Stilling et al, 2016). A recent clinical study found that reduced amounts of fecal butyrate, and butyrate-producing bacteria, were associated with increased depression symptoms in individuals with Parkinson's disease (Xie et al, 2022). This study also identified leukocyte genes whose methylation correlated with fecal butyrate levels in patients.…”
Section: Gut-brain Axismentioning
confidence: 80%
“…To connect these butyrate-associated changes in peripheral methylation to changes within the brain, the researchers compared the identified leukocyte genes to previous work that identified genes with altered methylation in prefrontal cortical neurons (Li et al, 2020). They found significant overlap and correlated likelihood of methylation in Parkinson's disease patients for the leukocyte and neuronal genes, suggesting the potential for decreased butyrate levels to contribute to neurological changes through effects on brain DNA methylation (Xie et al, 2022). Choline is a dietary source of one-carbon units for DNA methylation.…”
Section: Gut-brain Axismentioning
confidence: 99%
“…Faecalibacterium can maintain gut barrier function by producing the SCFA butyrate and secreting anti-inflammatory mediators (Lenoir et al, 2020). Lower levels of butyrate have been associated to postural instability, gait abnormalities, Movement Disorder Society-Sponsored Revised Unified Parkinson's Disease Rating Scale (MDS-UPDRS) part III motor scores, and depression in PD patients (Li et al, 2017;Xie et al, 2022). Surprisingly, Lactobacillus, Bifidobacterium, and Akkermansia levels are greater in PD patients (Nishiwaki et al, 2020), despite these bacteria are widely recognized as "beneficial", and often included in probiotic preparations (Tan et al, 2020).…”
Section: The Role Of the Microbiota-gut-brain Axis In Pdmentioning
confidence: 99%